Question
upstudy study bank question image url

Solve the equation: \( (x+3)^{2}+5(x+3)-6=0 \)

Ask by West Cervantes. in the United States
Dec 11,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x=-9 \) and \( x=-2 \).

Solution

Solve the equation \( (x+3)^{2}+5(x+3)-6=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(\left(x+3\right)^{2}+5\left(x+3\right)-6=0\) - step1: Expand the expression: \(x^{2}+11x+18=0\) - step2: Factor the expression: \(\left(x+2\right)\left(x+9\right)=0\) - step3: Separate into possible cases: \(\begin{align}&x+2=0\\&x+9=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=-2\\&x=-9\end{align}\) - step5: Rewrite: \(x_{1}=-9,x_{2}=-2\) The solutions to the equation \( (x+3)^{2}+5(x+3)-6=0 \) are \( x=-9 \) and \( x=-2 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let's simplify the equation by substituting \(y = x + 3\). Then the equation becomes: \( y^2 + 5y - 6 = 0 \) Now, we can factor this quadratic equation: \((y + 6)(y - 1) = 0\) This gives us two solutions: 1. \( y + 6 = 0 \) → \( y = -6 \) 2. \( y - 1 = 0 \) → \( y = 1 \) Now, revert back to \(x\): 1. For \(y = -6\): \(x + 3 = -6\) → \(x = -9\) 2. For \(y = 1\): \(x + 3 = 1\) → \(x = -2\) Thus, the solutions are \(x = -9\) and \(x = -2\).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy